Strengthening the Intercultural Competence continuum - Claudia Bulnes; Eveke De Louw (Forum Neue Medien in der Lehre Austria, 2017)
This article outlines a series of interventions aimed at strengthening the intercultural competence continuum of the European Studies programme of The Hague University of Applied Sciences (THUAS), in the Netherlands. It involved an analysis of all intended learning outcomes (ILOs) and a process to support lecturers in reformulating and internationalising these learning outcomes. The interventions resulted in a truly international degree programme but more importantly, and simultaneously, they contributed to the commitment to and engagement in internationalisation among lecturers. Thus, the case of THUAS demonstrates that increasing the skills of lecturers can also result in addressing another key blocker: their lack of engagement in internationalisation.